Venous Waveform Analysis Correlates With Echocardiography in Detecting Hypovolemia in a Rat Hemorrhage Model. (March 2021) - Lefevre, Ryan J.; Balzer, Claudius; Baudenbacher, Franz J.; Riess, Matthias L.; Hernandez, Antonio; Eagle, Susan S.
Background: Assessing intravascular hypovolemia due to hemorrhage remains a clinical challenge. Central venous pressure (CVP) remains a commonly used monitor in surgical and intensive care settings for evaluating blood loss, despite well-described pitfalls of static pressure measurements. The authors investigated an alternative to CVP, intravenous waveform analysis (IVA) as a method for detecting blood loss and examined its correlation with echocardiography. Methods: Seven anesthetized, spontaneously breathing male Sprague Dawley rats with right internal jugular central venous and femoral arterial catheters underwent hemorrhage. Mean arterial pressure (MAP), heart rate, CVP, and IVA were assessed and recorded. Hemorrhage was performed until each rat had 25% estimated blood volume removed. IVA was obtained using fast Fourier transform and the amplitude of the fundamental frequency (f1) was measured. Transthoracic echocardiography was performed utilizing a parasternal short axis image of the left ventricle during hemorrhage. MAP, CVP, and IVA were compared with blood removed and correlated with left ventricular end diastolic area (LVEDA). Results: All 7 rats underwent successful hemorrhage. MAP and f1 peak amplitude obtained by IVA showed significant changes with hemorrhage. MAP and f1 peak amplitude also significantly correlated with LVEDA during hemorrhage (R = 0.82 and 0.77, respectively). CVP did not significantly change with hemorrhage, and there was no significant correlation between CVP and LVEDA. Conclusions: In this study, f1 peak amplitude obtained by IVA was superior to CVP for detecting acute, massive hemorrhage. In addition, f1 peak amplitude correlated well with LVEDA on echocardiography. Translated clinically, IVA might provide a viable alternative to CVP for detecting hemorrhage.